Reutilization of Recycled Cellulose Diacetate From Discarded Cigarette Filters in Production of Stone Mastic Asphalt Mixtures - Liu, Huachen; Chen, Yikun; Xue, Yongjie (Frontiers in Materials, 2021)
In this paper, recycled cellulose diacetate (rCDA) derived from cigarette butts was used as a fiber stabilizer to develop stone mastic asphalt (SMA) mixtures. The characterizations of rCDA were investigated by scanning electron microcopy (SEM), a Fourier transform infrared spectrometer (FTIR), and a thermogravimetric analyzer (TGA). Volumetric stability, temperature stability, moisture stability, and fatigue performance of SMA mixtures with rCDA were tested to obtain the pavement performance. Results showed that rCDA appeared to have a tough surface texture with a curly and corrugated structure, which facilitated the enhancement of the cohesion bond with the asphalt binder. TG-DTG indicated that the maximum weight loss (62.48%) obtained at temperatures ranging from 294.1°C to 376.0°C was due to decomposition and degradation of organic matters. When 0.4% rCDA was used in the asphalt mixture, the dynamic stability was 4,105 cycles/mm. The ultimate flexural strength and flexural stiffness modulus were 3,722 MPa and 9.7 MPa. It indicated that the temperature stability of 0.4% rCDA was superior to 0.3% polyacrylonitrile fiber (PAN), while inferior to 0.3% polyester (PET). The value of tensile strength ratio and residual Marshall stability were 80.2 and 75.3%, respectively. The fatigue life of 0.4% rCDA was technically like that of 0.3% PAN and 0.3% PET at lower stress levels. All results concluded that the optimum content of rCDA in asphalt mixtures was 0.4% by mass of the binder.